Pendekatan Komunikatif dalam Al-Quran - Ali Fikri Noor (LP2M Universitas PTIQ Jakarta, 2018)
The phenomenon of the Qur’anic sciences has fostered the spirit of scientists to continue to explore the miraculous side of the Qur’an in all its dimensions, both from the review of biology, physics, geology, astronomy, discipline and other fields of study. new disciplines are: at-Tafsir al-Ilmy at-Tajribi. The interesting scientific study of the Qur’an is also the theme of the Qur’an and communication, about this side Sayid Qhutub (1980) once explained: “Regarding differences in languages and skin colors, differences in character ( character or character, and morality, differences in talents and potentials, then all of that is diversity (Variety/Tanawwu‘) which cannot cause discord and division, but it requires mutual cooperation towards the resurrection of all burdens and require fulfillment for all purposes “. Among the results of conclusions that can be learned through the Qur’an and communication studies are that the ways of communicating taught by the Qur’an t urned out to be diverse, both in the style of language used, also in the delivery situation, respectively. each has an ideal and proportional place. Like communication with Qaulan Ma’rufa, Qaulan Sadida, Qaulan Karima, Qaulan baligho, Qaulan Layyina, Qaulan Maysuura, and Qaulan Tsaqila. In the view of the experts the interpretation of all the expressions of these words has different dimensions of meaning and understanding between one another.